(3CSGSjGJ JObjb fXe GdeYdheGJ aj GdeDSSIs - (3eHShW(B, (3ghGQjIs ((3GdLRGFQs (3OGQ GdHGMK ddfTQ hGdETgGQs, 2023)
(3fXe hJcfhdhLjG GdeYdheGJ, JObjb fXe GdeYdheGJ hYdGbJg HGdJObjb GdGdcJQhfjefgG JObjb fXe GdeYdheGJ, hGdeMGSHI GdGdcJQhfjI, cPdc GdaQb hGdYdGbI eGHjf GdJObjb GdGdcJQhfjhJObjb fXe GdeYdheGJ(B.(3hCNjQG GdJObjb aj Xd GdJLGQI GdGdcJQhfjI(B.s
Keywords: (3GdJObjbs; (3eQGLYI GdMSGHGJs; (3fXe GdeYdheGJs